Impact of climate change on indoor environment of historic libraries in Mediterranean climate zone. (18th July 2019) - Turhan, Cihan; Arsan, Zeynep Durmus; Akkurt, Gulden Gokcen
Most historic library buildings house valuable paper-based collections that are kept in unconditioned environments. This vulnerable cultural heritage is expected to be highly affected by climate change in the future. In this study, indoor microclimate of an unconditioned historic library, Necip Paşa Library (Izmir, Turkey) is analysed for existing conditions and future climate data. The measured and predicted indoor microclimate data from 'present' till 2080s are used to determine possible chemical degredation risk on library collection and human comfort. Comparison of periodic results of future climate data indicates an increase in temperature that could cause both an increase in chemical degredation risk on the library collection and a decline in thermal comfort conditions. Mitigation of climate change effects on library collection and human comfort requires taking some actions such as adding light and adaptive mechanical solutions.